Peroral endoscopic myotomy for esophageal motility disorders - Feng, Jie; Ali, Raja Waqar; Hao, Jin-yong; Kong, Gui-xiang; Yang, Li-hong; Huang, Xiao-jun (Esophagus : official journal of the Japan Esophageal Society, 2020)
Background Esophageal motility disorders which include achalasia, esophagogastric junction outflow obstruction (EGJ outflow obstruction), jackhammer esophagus (JE), distal esophageal spasm (DES), etc. are rare disease of unknown causes. The diagnosis is based on endoscopy, barium meal, and high-resolution manometry (HRM). With the development of endoscopy, peroral endoscopic myotomy (POEM) has emerged as a standard method for the treatment of achalasia. Purpose The purpose of this article is to enable gastroenterologists to have a more comprehensive understanding of the application status, technical characteristics, clinical efficacy and future prospect of POEM in the treatment of esophageal motility disorders. Methods Through a large number of reading literature, combined with clinical practice, summary and analysis of the indications, procedure, efficacy, complications, and controversies of POEM in the treatment of esophageal motility disorders, as well as the current and future perspectives of POEM were studied. Results POEM is safe and effective in the treatment of esophageal motility disorders, but the GERD reflux rate is higher. Conclusions POEM can be a new option for the treatment of esophageal movement disorders, but large sample, multi-center, long-term study reports are needed, and it promotes the development of NOTES technology.